PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PERBANKAN PERIODE 2020-2022 : PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PERBANKAN PERIODE 2020-2022 - Lanang Prayoga; Ermina Sari; Erni Febriani (Sekolah Tinggi Ilmu Ekonomi Al-Madani, 2025)
During the PSBB period, the financial sector index and banking index recorded a sharp decline, with some large banking stocks even approaching the Auto Reject Lower (ARB) limit. This instability continued until 2022, indicating a challenge in maintaining the performance of banking stocks amid changing market dynamics. The aim of this research is to determine the effect of financial ratios on share prices of banking companies on the Indonesia Stock Exchange in 2020 - 2022. This type of research is quantitative research with secondary data. Data collection techniques are internet research and documentation studies. The sampling technique used purposive sampling to produce 33 banking companies from a total of 47 banking companies. The data processing used is Panel Data Regression. Based on the results of the analysis of the influence of financial ratios on share prices in 2020 - 2022, the author finds that the Return On Equity and Capital Adequacy Ratio variables have a significant positive influence on share prices, while the Debt to Equity Ratio variable has a negative influence on share prices, whereas the variables earnings per share and return on assets do not have a significant influence on share prices.